2016
DOI: 10.1016/j.aop.2016.07.011
|View full text |Cite
|
Sign up to set email alerts
|

Wigner transformation, momentum space topology, and anomalous transport

Abstract: Using derivative expansion applied to the Wigner transform of the two - point Green function we analyse the anomalous quantum Hall effect (AQHE), and the chiral magnetic effect (CME). The corresponding currents are proportional to the momentum space topological invariants. We reproduce the conventional expression for the Hall conductivity in $2+1$ D. In $3+1$ D our analysis allows to explain systematically the AQHE in topological insulators and Weyl semimetals. At the same time using this method it may be prov… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
146
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 54 publications
(154 citation statements)
references
References 69 publications
8
146
0
Order By: Relevance
“…The meaning of Q(p) for the lattice models of electrons in crystals is the inverse propagator of Bloch electron. Introduction of an external gauge field A(x) defined as a function of coordinates effectively leads to the Peierls substitution (see, for example, [38,78,79]):…”
Section: A Lattice Model In Momentum Spacementioning
confidence: 99%
See 2 more Smart Citations
“…The meaning of Q(p) for the lattice models of electrons in crystals is the inverse propagator of Bloch electron. Introduction of an external gauge field A(x) defined as a function of coordinates effectively leads to the Peierls substitution (see, for example, [38,78,79]):…”
Section: A Lattice Model In Momentum Spacementioning
confidence: 99%
“…The previous definitions of the Wigner-Weyl formalism (used earlier for the description of the quantum Hall effect), [78,79], given for completeness in Appendix B and Appendix C, are sufficient for the description of the systems in the presence of slowly varying fields. This assumes, in particular the requirement for the real crystals that the magnetic field is much smaller than about 10000 Tesla.…”
Section: A Lattice Wigner-weyl Calculus Through the Series Expansionmentioning
confidence: 99%
See 1 more Smart Citation
“…It satisfies the Groenewold equation Q W (R, p) ⋆ G W (R, p) = 1 [13,38], where Q W is the Weyl symbol of operatorQ,…”
Section: Wigner Transform and The Model Under Considerationmentioning
confidence: 99%
“…In the works of one of the authors of the present paper the Wigner-Weyl formalism has been applied to the study of the nondissipative transport phenomena [47][48][49][50][51][52]. In particular, it was shown that the response of nondissipative currents to the external field strength is expressed through the topological invariants that are robust to the smooth deformations of the system.…”
Section: Introductionmentioning
confidence: 99%